1994
DOI: 10.1063/1.357616
|View full text |Cite
|
Sign up to set email alerts
|

Al-O interactions in ion-implanted crystalline silicon

Abstract: The formation and dissolution of Si-O-Al precipitates have been investigated in Czochralski silicon wafers implanted with 6 MeV Al ions and thermally processed. The data have been compared to the O precipitation in samples implanted with 6 MeV Si or P ions. The amount of precipitated O atoms is about one order of magnitude higher for Al than for Si or P implanted samples. Moreover, a strong gettering of the Al atoms by the silicon dioxide precipitates has been observed. The precipitate evolution has been studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…3 The Al solid solubility in Si is quite low (1 ϫ 10 19 cm Ϫ3 at 900ЊC 4 ); however, even at a concentration below solid solubility, Al x O y precipitates are formed due to the high reactivity of Al with the oxygen present in the Czochralski grown wafers (oxygen content 10 18 cm Ϫ3 ). 5 No precipitation occurs if implants are performed into epitaxially grown Si, where the oxygen content is less than 1 ϫ 10 16 cm Ϫ3 , and the Al concentration does not exceed the solid solubility limit. However, the oxygen concentration can be high also in epi layers after an oxidation process due to the oxygen drive-in and diffusion from the surface to the bulk.…”
mentioning
confidence: 99%
“…3 The Al solid solubility in Si is quite low (1 ϫ 10 19 cm Ϫ3 at 900ЊC 4 ); however, even at a concentration below solid solubility, Al x O y precipitates are formed due to the high reactivity of Al with the oxygen present in the Czochralski grown wafers (oxygen content 10 18 cm Ϫ3 ). 5 No precipitation occurs if implants are performed into epitaxially grown Si, where the oxygen content is less than 1 ϫ 10 16 cm Ϫ3 , and the Al concentration does not exceed the solid solubility limit. However, the oxygen concentration can be high also in epi layers after an oxidation process due to the oxygen drive-in and diffusion from the surface to the bulk.…”
mentioning
confidence: 99%
“…It has been demonstrated in previous works that precipitation occurs where damage, aluminum, and oxygen are simultaneously present. [2][3][4] To understand the phenomenon taking place during oxidation, the injected oxygen distribution has been calculated using the model described in Ref. 11.…”
Section: Resultsmentioning
confidence: 99%
“…The main problems associated with the use of Al implants, however, are the outdiffusion from the sample during the driving process 1 and its reactivity with oxygen atoms. 2,3 The latter phenomenon causes Al precipitation in proximity to the implant-induced defects that act as nucleation centers for the formation of Al x O y clusters. This occurs in Czochralski-grown substrates where the bulk oxygen concentration is about 8ϫ10 17 atom/cm 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of these precipitates and their evolution as a function of the diffusion time and temperature has been previously investigated. 3 It was found that the amounts of A1 and O into the precipitates follow the same trend revealing a strong interaction between the SiO2 precipitates and the implanted aluminum. This phenomenon is mainly observed on Czochralski-grown silicon wafers where the oxygen bulk concentration is about 8 X 10~7/cm 3.…”
Section: Introductionmentioning
confidence: 87%